PENGARUH PENJUALAN SECARA ONLINE TERHADAP MINAT BELI MASYARAKAT KOTA KENDARI - Zainuddin, Muh. Zabir; Destiani, Tina; Manan, La Ode Abd. (Sultra Journal of Economic and Business, 2020)
The purpose of this study is to determine whether online sales have a significant effect on people's interest in buying Syar'i hijab clothing products at the “Emmy Hijabku” Clothing Store Kendari.The problem in this study is whether online sales have a significant effect on people's interest in buying Syar'i hijab fashion products at “Emmy Hijabku” Clothing StoreBy using a simple linear regression equation with the formulation Y = a +bX the results of the data analysisobtained Y = 8,071 + 0.640X. From the results of the study found that online syar'i hijab sales variables significantly influence the buying interest of the people in Kendari.It simply can be seen from a significant online sales label of 0.001, which means smaller than the significant level used is 0.05 and can be seen also from t-count with a value of 3,656 which means t-count is greater than t-table which is 0.681.